The Success of Acquisitions: Evidence from Divestitures - Kaplan, Steven N.; Weisbach, Michael S. (Journal of Finance, 1992)
This paper studies a sample of large acquisitions completed between 1971 and 1982. By the end of 1989, acquirers have divested almost 44% of the target companies. We characterize the ex post success of the divested acquisitions and consider 34% to 50% of classified divestitures as unsuccessful. Acquirer returns and total (acquirer and target) returns at the acquisition announcement are significantly lower for unsuccessful divestitures than for successful divestitures and acquisitions not divested. Although diversifying acquisitions are almost four times more likely to be divested than related acquisitions, we do not find strong evidence that diversifying acquisitions are less successful than related ones.